Life strategy and grazing intensity responses of Brachionus calyciflorus fed on different concentrations of microcystin-producing and microcystin-free Microcystis aeruginosa - Liang, Ye (Sci Rep, 2017)
The occurrence of Microcystis blooms is a worldwide concern due to the numerous adverse effects on zooplankton. We therefore hypothesized that the cyanobacterium Microcystis aeruginosa is harmful to rotifer growth. Population and individual experiments were conducted with the same proportional volumes of Chlorella and Microcystis for given food densities. Life-table parameters, life-history traits, and the grazing intensity of Brachionus calyciflorus were evaluated after they had fed on microcystin-producing and microcystin-free Microcystis, both alone and combined with an edible alga (Chlorella pyrenoidosa), at concentrations of 1 × 10(5), 1 × 10(6), and 1 × 10(7) cells mL(−1). The results showed that the interactive effects of food density and type appeared to be synergistic on generation time (T), net reproduction rate (R(0)), body length, swimming speed, and reproduction time. In contrast, these effects appeared to be antagonistic on intrinsic growth rate (r), finite rate of increase (λ), time to first brood, post-reproductive time and total offspring per female. The grazing rate of rotifers decreased with grazing time. Although the toxins released after grazing on M. aeruginosa had negative effects on rotifer growth and reproduction, B. calyciflorus changed its life strategy and grazing intensity in response to eutrophic conditions.